Ireland : Staff Report for the Third post-Program Monitoring Discussions. (IMF Staff Country Reports; Country Report, 2015)
This paper discusses the recommendations of Third Post-Program Monitoring Discussions with Ireland. Ireland's strong economic recovery is continuing in 2015, following robust growth of 4.8 percent in 2014. A range of high frequency indicators point to an extension of the solid recovery momentum into 2015, with growth increasingly driven by domestic demand as well as exports. Financial conditions remain highly supportive despite some recent bond market volatility. Ireland's economic rebound is in full swing, yet fiscal restraint must be maintained in 2015. Fiscal policy should make solid progress toward balance in the favorable economic environment, and the limited fiscal space in coming years should be used to support durable growth.